# Find the middle term in the expansion of :(i) (3 + x)6(ii) (iii) (iv) (i) For (3 + x)6,

a=3, b=x and n=6

As n is even, is the middle term

Therefore, the middle term General term tr+1 is given by, Therefore, for 4th , r=3

Therefore, the middle term is   = (20). (27) x3

= 540 x3

(ii) For , , b=3y and n=8

As n is even, is the middle term

Therefore, the middle term General term tr+1 is given by, Therefore, for 5th , r=4

Therefore, the middle term is     = (70). x4 y4

(iii) For , , and n=10

As n is even, is the middle term

Therefore, the middle term General term tr+1 is given by, Therefore, for 6th , r=5

Therefore, the middle term is     = -252

(iv) For ,

a=x2, and n=10

As n is even, is the middle term

Therefore, the middle term General term tr+1 is given by, Therefore, for the 6th middle term, r=5

Therefore, the middle term is     = -252 (32) x5

= -8064 x5

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.